Numerical simulation of Microfluidic devices - Uda, Hashim, Prof. Dr.; P.N A. Diyana; Tijjani Adam, Shuwa (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org